2011
DOI: 10.1371/journal.pone.0021176
|View full text |Cite
|
Sign up to set email alerts
|

Id1 Interacts and Stabilizes the Epstein-Barr Virus Latent Membrane Protein 1 (LMP1) in Nasopharyngeal Epithelial Cells

Abstract: The EBV-encoded latent membrane protein 1 (LMP1) functions as a constitutive active form of tumor necrosis factor receptor (TNFR) and activates multiple downstream signaling pathways similar to CD40 signaling in a ligand-independent manner. LMP1 expression in EBV-infected cells has been postulated to play an important role in pathogenesis of nasopharyngeal carcinoma. However, variable levels of LMP1 expression were detected in nasopharyngeal carcinoma. At present, the regulation of LMP1 levels in nasopharyngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…LMP1 protein in the cell may be unstable and easily degraded. Notably, LMP1 is reported to be degraded rapidly through the ubiquitin/proteasome-dependent pathway (67), and LMP1 degradation is specifically regulated in NPC cells (45). Furthermore, since LMP1 mRNA levels are low in C666-1 cells, LMP1 may be regulated prior to its translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMP1 protein in the cell may be unstable and easily degraded. Notably, LMP1 is reported to be degraded rapidly through the ubiquitin/proteasome-dependent pathway (67), and LMP1 degradation is specifically regulated in NPC cells (45). Furthermore, since LMP1 mRNA levels are low in C666-1 cells, LMP1 may be regulated prior to its translation.…”
Section: Discussionmentioning
confidence: 99%
“…HEK293EBV-BAC and HeLa-CR2/GFP-EBV (32) cells were maintained in Dulbecco modified Eagle medium (Sigma) supplemented with 10% fetal bovine serum. Akata(Ϫ), C666-1 (45), and LCLs were maintained in RPMI 1640 medium supplemented with 10% fetal bovine serum. Antibodies against SP1 and PAX5 were obtained from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%
“…Ubiquitination and proteasome-dependent degradation of LMP1 is further dependent on the TRAF-binding site within the carboxy-terminus of LMP1 (Rothenberger et al 2003;Hau et al 2011). Mutation of the amino-terminus showed that this domain does not contribute critical signals for B cell transformation (Izumi et al 1994;Dirmeier et al 2003).…”
Section: Amino-terminus and Transmembrane Domainmentioning
confidence: 99%
“…TRAFs are thought to interact with CD 40 to nuclear factor (NF)-κB and c-Jun kinase (JNK) activation. Similar to CD 40 , LMP1 also binds TRAFs which are then thought to interact with kinases such as NF-κB-inducing kinase that ultimately promote activation of NF-κB (33)(34)(35)(36)(37)(38). However, further investigation on the exact interaction between LMP1 and miRNA-146a is still needed.…”
Section: Discussionmentioning
confidence: 99%